Advanced bottom-up engineering of living architectures - Gaspar, Vítor M. (2022)
Bottom-up tissue engineering is a promising approach for designing modular biomimetic structures that aim to recapitulate the intricate hierarchy and biofunctionality of native human tissues. In recent years, this field has seen exciting progress driven by an increasing knowledge of biological systems and their rational deconstruction into key core components. Relevant advances in the bottom-up assembly of unitary living blocks toward the creation of higher order bioarchitectures based on multicellular-rich structures or multicomponent cell–biomaterial synergies are described. An up-to-date critical overview of long-term existing and rapidly emerging technologies for integrative bottom-up tissue engineering is provided, including discussion of their practical challenges and required advances. It is envisioned that a combination of cell–biomaterial constructs with bioadaptable features and biospecific 3D designs will contribute to the development of more robust and functional humanized tissues for therapies and disease models, as well as tools for fundamental biological studies.